Transmission mode ultrasonic tomography to identify liquid or solid flow regime - Iskandar Rizan, Muhamad (2012)
This project is to develop a suitable ultrasonic tomography system that can identify water and solid flow regime. This project presents the application of the ultrasonic tomography in the process and chemical industries. The transmission mode with fan shaped beam projection had been implemented. The system is designing non-invasively that mean the composition in the system can be monitored without disturbing the nature of process in the pipe. The transmission mode for sensing purpose was implemented by using 4 sensors for transmitters and 4 sensors for receivers where 4x4 projections were produced. This project is divided into two parts which are hardware and software. The hardware part for electronic measurement circuit and fabrication of ultrasonic sensor. For software part is coding to microcontroller and circuit design. The experiments had been conducted show that the suitable ultrasonic tomography system can identify water and solid flow regime.